Estudio para el mejoramiento de los sistemas administrativos de la empresa "Isabella". - Castillo Liuba, Jefferson Francisco (2013)
The thesis: "Investigation for the optimization of Business Administrative Systems ISABELLA, includes: research’s contextual, theoretical framework, research methodology, results, conclusions, recommendations, bibliography and appendices. Chapter I, Contextual Research, raised the overall objective of the research was to conduct a study for the improvement of the Management Systems ISABELLA Company, leading to pursuit the following specific objectives as part for development researching: Develop a diagnosis of the current situation of the company (SWOT analysis) and propose a model for Enterprise Management System "ISABELLA" Chapter II, Theoretical Framework is taken as reference for the development of research concepts, importance, elements, and characteristics of strategic planning in small organizations based on authors such as SÉRVULO - 2010, BATEMAN-SNELL 2009, FRED R DAVID 2008, among others. The SWOT Matrix study is of paramount importance in Strategic Planning, by reference to its relevant concepts (LOURDES MÜNCH - 2007, CHIAVENATO 2005, FRED R DAVID 2008), to deepen their study and analyzing the theories for the correct SWOT analysis application.